Peningkatan Literasi Perbankan Syariah pada Masyarakat Kelurahan Sambiroto - Rhealin Hening Karatri; Dhaifina Idznitia Apriyani Naimi (Muria Jurnal Layanan Masyarakat, 2023)
The development of the times has made the financial industry faster in innovating. Financial institutions are currently not only engaged in conventional financial institutions but there are Islamic financial institutions. One of the Islamic financial institutions that has developed to date is Islamic banking. The services of Islamic financial institutions are sometimes not understood by the public. The public's understanding of various Islamic banking literature needs to be clarified by providing an easy to understand example for people starting from the lower middle class or even the upper class. The purpose of this service is to provide Islamic banking literacy to the people in Sambiroto Village for Islamic banking products in various Sharia Banks in Indonesia. As a result of this service, it is hoped that the people of Sambiroto Village can better understand and understand the literature of Islamic banking and even want to transact in Islamic banking.